2015
DOI: 10.3356/rapt-49-02-183-191.1
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Ecology and Distribution of White-rumped Vultures (Gyps bengalensis) in Himachal Pradesh, India

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Cliff-breeding species often congregate with up to almost one thousand pairs in a colony in the Cape Griffon Gyps coprotheres in southern Africa (Mundy et al 1992) or more than a hundred pairs in the Eurasian Griffon G. fulvus in southern Europe (Slotta-Bachmayr et al 2005). In tree-breeding species, colonial breeding is unusual but found for example in White-rumped Vulture Gyps bengalensis in Asia (Thakur 2015). White-backed Vultures are widespread in sub-Saharan Africa and nest exclusively in large trees throughout their range.…”
mentioning
confidence: 99%
“…Cliff-breeding species often congregate with up to almost one thousand pairs in a colony in the Cape Griffon Gyps coprotheres in southern Africa (Mundy et al 1992) or more than a hundred pairs in the Eurasian Griffon G. fulvus in southern Europe (Slotta-Bachmayr et al 2005). In tree-breeding species, colonial breeding is unusual but found for example in White-rumped Vulture Gyps bengalensis in Asia (Thakur 2015). White-backed Vultures are widespread in sub-Saharan Africa and nest exclusively in large trees throughout their range.…”
mentioning
confidence: 99%
“…In India, white-rumped vultures use chir pine (Pinus roxburghii) for nesting in Himanchal Pradesh (Thakur, 2015), coconut palm (Cocos nucifera), mango (Magnifera species) and Termenalia in Western Maharashtra (Majgaonkar et al, 2018), and white murdah (T. arjua) in Tamilnadu (Ramakrishnan et al, 2014). It appears that white-rumped vultures preferred certain trees irrespective of the diversity and availability of other trees.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, three out of nine vulture species, namely red‐headed vulture ( Sarcogyps calvus ), slender‐billed vulture ( Gyps tenuirostris ), and white‐rumped vulture ( G. bengalensis ) are typically tree nesters while the Egyptian vulture ( Neophron percnopterus ) builds nests on trees on rare occasions (Ali & Ripley, 1987 ; Chhangani, 2002 ). These species require mature and tall trees for nesting (Ahmad et al., 2020 ; Ghimire et al., 2019 ; Majgaonkar et al., 2018 ; Siders & Kennedy, 1996 ; Thakur, 2015 ). The wild vulture population has been declining in South Asia due to the use of diclofenac in veterinary practices (Ahmad et al., 2020 ; Chaudhary et al., 2012 ; Khan, 2013 ; Prakash et al., 2007 ), food shortage (Shah et al., 2019 ), unintentional poisoning (Clements et al., 2013 ), human persecution (Clements et al., 2013 ; Hla et al., 2011 ), collision with power lines and electrocution (Hamal et al., 2023 ), and breeding habitat loss (Gautam & Baral, 2013 ; Hla et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many earlier studies on vultures also reported the continuous use of the same nesting site for many years (Rasmussen and Anderton, 2005;Davit, 2009;Kushwaha et al, 2009;Kanaujia et al, 2010;Vergara et al, 2010). Despite their declining status, since 2000, long-term studies on breeding ecology, an essential aspect to understand their reproductive performance in recent years, are still rare on WRV (Gill, 1921;Thakur, 2015;Samson and Ramakrishnan, 2020) and LBV (Kulshreshtha, 2001;Rasmussen and Anderton, 2005;Naoroji, 2007;Kushwaha et al, 2009;Kanaujia et al, 2013;Khatri, 2015;McClure et al, 2021). In this paper, we present long-term data collected from 2010 to 2021 on the breeding ecology, which includes breeding phenology and reproductive performance of Long-billed vulture and White-rumped vulture from Kaghaznagar Forest Division and its adjoining areas in the Deccan Plateau, India.…”
Section: Introductionmentioning
confidence: 99%